2143. Incidence of Infection in Patients Receiving Short vs. Long Duration of Antimicrobial Prophylaxis in Neurosurgery. (26th November 2018) - Bast, Chelsea; Colley, Peter; Roth, Jennifer; Nguyen, Hoa; Naftalis, Richard; Berhe, Mezgebe
Abstract: Background: Surgical site infections in neurosurgery occur in up to 10% of procedures. The American Society of Health-System Pharmacists guidelines promote antimicrobial prophylaxis (AP) for up to 24 hours from neurosurgery using cefazolin while the Neurocritical Care Society guidelines promote single pre-procedural dose of AP for extraventricular drain (EVD) monitoring. Despite these guidelines, practice variation exists with often longer antimicrobial exposure and subsequent complications. Methods: This retrospective study included patients admitted to Baylor University Medical Center from January 1, 2014 to September 20, 2017 and underwent cranial or spinal neurosurgery requiring AP. This study excluded patients with basilar skull fracture, presence of cerebrospinal fluid leak, penetrating trauma, meningitis, and patients receiving antibiotics for documented or suspected infection unrelated to neurosurgery. Patients who received AP for up to 24H (short course) were compared with patients who received AP for greater than 24H (long course) at 90 days. Data were analyzed using the Fisher exact test, Student's t -test and Wilcoxon rank-sum tests as applicable. Results: A total of 183 patients were included with 90 and 93 patients receiving short or long courses of AP, respectively. Baseline characteristics were similar for the groups. Patients in the short course AP group received a mean antibiotic duration of 16.9 ± 4.3H while those in the long course AP group received 72.2 ± 50.9H ( P < 0.001). The mean number of antimicrobials prescribed was 1.1 vs. 1.8 ( P < 0.001) in the short vs. long groups, respectively. At 90 days, there were no significant differences in the rate of surgical site infections (1.1% vs. 2.1%, P = 0.99), development of multi-drug-resistant infections (2.2% vs. 2.2%, P = 0.99), and Clostridium difficile infection (0% vs. 1.1%, P = 0.99) in the short vs. long groups, respectively. Conclusion: The rate of surgical site infections was not significantly different in patients that received short vs. long durations of antimicrobial prophylaxis. These results highlight an opportunity to improve antibiotic use and promote principles of antimicrobial stewardship in neurosurgery. Disclosures: All authors: No reported disclosures.